The Effect Of Workload On Audit Quality (Empirical Study at the Sumedang District Regional Inspectorate) - Maliyah, Nalia; Hidayat, Gustina; Krisdina, Tiana Fenny (SINTESA, 2025)
This study aims to empirically test the effect of workload on audit quality at Sumedang District Inspectorate. The background of the study is based on the imbalance between the number of auditors and the number of objects of supervision, which has an impact on the emergence of findings that have not been followed up. The population in this study were all staff of Sumedang District Inspectorate, totaling 65 people. The sample in this study was 22 auditors selected through purposive sampling techniques. Data collection was carried out through questionnaires, interviews and documentation. The analysis techniques used were data quality testing, classical assumption testing and simple linear regression using IBM Statistic software version 25. The results of the study showed that workload had a significant negative effect on audit quality with a t count of 2.150 > t table of 2.086 and a coefficient on workload of -0.019, meaning H1 was accepted. Therefore, high workload can decrease audit quality